Kant on melancholy: philosophy as a relief to the disgust for life - Feloj, Serena (Con-Textos Kantianos. International Journal of Philosophy, 2021)
Melancholy occupies a privileged place in the Kantian taxonomy of temperaments since the pre- critical phase, but it is in the Nineties that it reveals its philosophical fecundity. Melancholy becomes, in fact, an interesting notion not so much because of its relationship with Kantian biography, nor because of its presence in the description of psychopathies, but because it lies, unique in this, on the borderline between pathology and sanity. Melancholy thus provides an opportunity to show the topicality of Kantian reflection on mental illness since it underlines the continuity, and not the rupture, between the healthy mental state and that affected by illness, in line with today’s most widespread tendencies to consider mental illness as a privileged observatory of the subject.